Acetabular Fracture Resulting from a Basketball Cutting Movement in a Young Adult Male: A Case Report. Issue 4 (October 2019) - Sperring, Thomas R.; Only, Arthur J.; Wintermeyer, Elke; DeRogatis, Michael J.; Issack, Paul S.
Abstract : Case: We present the case of a 26-year-old man who sustained a right transverse-posterior wall acetabular fracture while performing a cutting movement playing basketball. Conclusions: Acetabular fracture after a relatively low-energy injury in a healthy young adult male is an extremely unusual event. The cutting movement to the right likely forcefully placed the right hip in flexion, adduction, and internal rotation directing the femoral head into the posterior wall. The patient had excellent clinical and radiographic results after acetabular open reduction and internal fixation.